2018
DOI: 10.1111/2041-210x.12988
|View full text |Cite
|
Sign up to set email alerts
|

On the universality of target‐enrichment baits for phylogenomic research

Abstract: Capturing conserved genomic elements to shed light on deep evolutionary history is becoming the new gold standard for phylogenomic research. Ultraconserved elements are shared among distantly related organisms, allowing the capture of unpreceded amounts of genomic data of non‐model taxa. An underappreciated consequence of hybrid enrichment methods is the potential of introducing undetected DNA sequences from organisms outside the lineage of interest, facilitated through the high degree of conservation of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 41 publications
2
38
0
Order By: Relevance
“…Bossert and Danforth () demonstrated that some UCE loci are shared across all arthropod UCE probe sets designed to date and correspond to genes with known function. Similarly, the vast majority (>98%) of arachnid UCEs were shown to be exonic in origin and annotated to genes with known functions (Hedin et al, ), making sequence capture of UCEs in arachnids essentially exon capture with the potential sequencing of adjacent intronic regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bossert and Danforth () demonstrated that some UCE loci are shared across all arthropod UCE probe sets designed to date and correspond to genes with known function. Similarly, the vast majority (>98%) of arachnid UCEs were shown to be exonic in origin and annotated to genes with known functions (Hedin et al, ), making sequence capture of UCEs in arachnids essentially exon capture with the potential sequencing of adjacent intronic regions.…”
Section: Discussionmentioning
confidence: 99%
“…Other considerations may certainly help locus recovery, including adjustments to the hybridization protocol (Li, Hofreiter, Straube, Corrigan, & Naylor, 2013;Paijmans, Fickel, Courtiol, Hofreiter, & Förster, 2016) and deeper sequencing, particularly for extremely important specimens (e.g., type or rare specimens). Bossert and Danforth (2018) demonstrated that some UCE loci are shared across all arthropod UCE probe sets designed to date and correspond to genes with known function. Similarly, the vast majority (>98%) of arachnid UCEs were shown to be exonic in origin and annotated to genes with known functions , making sequence capture of UCEs in arachnids essentially exon capture with the potential sequencing of adjacent intronic regions.…”
Section: Practical Considerationsmentioning
confidence: 97%
“…Cleaned and trimmed reads were inspected for quality using fastqc (Andrews, 2010), then assembled into contigs with spades 3.7.1 (Bankevich et al, 2012). Using phyluce, the Adephaga 2.9Kv1 UCE probes were matched to the assembled contigs with a minimum identity of 82% so as to avoid off-target contaminating sequences (Bossert & Danforth, 2018) and the UCE loci were extracted. Using phyluce, UCE loci were then aligned with mafft 7.215 (Katoh & Standley, 2013) and internally trimmed with gblocks 0.91 (Castresana, 2000;Talavera & Castresana, 2007).…”
Section: Sequence Generation and Data Processingmentioning
confidence: 99%
“…Capitalizing on recent technological advancements, the hybrid capture approach has been steadily gaining traction over the last decade (Bossert & Danforth, 2018; Bragg, Potter, Bi, & Moritz, 2016; Faircloth et al, 2012; Lemmon, Emme, & Lemmon, 2012). Principally, DNA or RNA probes are designed based on conserved sequences within the genome and used to hybridize to these targeted loci in a DNA library that are subsequently enriched and sequenced.…”
Section: Introductionmentioning
confidence: 99%